2005
DOI: 10.1007/s00429-004-0445-7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the origin and development of the appendices of the testis and epididymis in humans

Abstract: Hydatids, as appendices of testis or epididymis, were discovered by Morgagni in 1703 and 1705 and published by him in 1761. Hydatids are considered to be remnants of the cranial part of the Mullerian duct (MD), Wolffian duct (WD), or mesonephric tubules. They are localized as sessile or pedunculated appendices at the cranial pole of testis and at the head of epididymis, or at analogous organs in women. The clinical relevance is known: acute scrotum with torsion of appendices, or metaplasia. However, little is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Another hypothesis suggests that the surface epithelium, subepithelial capillaries and lymphatic vessels of testicular appendices form a functional unit (8). Some studies have analyzed the embryology (9) and structure of the testicular and epididymal appendices (3,10).…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis suggests that the surface epithelium, subepithelial capillaries and lymphatic vessels of testicular appendices form a functional unit (8). Some studies have analyzed the embryology (9) and structure of the testicular and epididymal appendices (3,10).…”
Section: Introductionmentioning
confidence: 99%
“…The exact role of this hydatid is unclear, there are only a few reports that discuss the possible functions of AT in humans. Holstein assumed that the AT controlled the amount of serous fluid within the space of the tunica vaginalis, 2 while another theory suggested that the epithelial layer together with subepithelial capillaries and lymphatic vessels form a functional unit 3…”
Section: Introductionmentioning
confidence: 99%
“…The epididymides show typical characteristics of highly coiled ducts lined by tall columnar cells, whereas the vasa deferentia have a slightly folded mucosa and a thick muscular coat consisting of three layers 12 . These androgen‐stimulated structures are distinct from Wolffian and Müllerian remnants, which can be found in both sexes and are thought to represent vestigial parts of the common genital ducts that have failed to regress completely 15 . Severe AIS is associated with AR mutations that retain very low but significant residual activity, sufficient to cause male differentiation only in the local environment surrounding the testis, where testosterone concentrations are estimated to be at least 100 times higher than in the circulation 12,16 …”
Section: Discussionmentioning
confidence: 99%